La orientación cristológica de la tradición sobre Jesús - Guijarro Oporto, Santiago 1957- (2010)
This paper studies the development of the Jesus’ tradition. It starts by asking to what extent the changes that occurred along this process affected the understanding of the memories about him that were preserved and handed over. To answer this question some representative examples of three crucial moments in this process are examined: the first patterning of such memories in the oral tradition, the formation of the sources used by the evangelists, and the composition of the Gospels. The examples discussed show that the process of formation and transmission of the memories about Jesus was governed by a Christological concern, namely to find a more precise answer to the question about the identity of Jesus.
Este artículo estudia la evolución que experimentó la tradición sobre Jesús. Comienza preguntándose en qué medida los cambios que se produjeron en dicho proceso afectaron a la comprensión de los recuerdos que se conservaban y transmitían sobre él. Para responder a esta pregunta se examinan algunos ejemplos representativos de tres momentos cruciales en este proceso: la primera formulación de dichos recuerdos en la tradición oral, la formación de las fuentes utilizadas por los evangelistas, y la composición de los evangelios. Los ejemplos examinados muestran que el proceso de fijación y transmisión de los recuerdos sobre Jesús estuvo guiado por una preocupación cristológica: encontrar una respuesta cada vez más precisa a la pregunta por la identidad de Jesús.
Keywords: género biográfico; fuentes evangélicas; tradición oral; Cristología